2016
DOI: 10.1097/ijg.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Intraocular Pressure in Patients Undergoing Penetrating Keratoplasty and Descemet Stripping Endothelial Keratoplasty

Abstract: Elevation of IOP is a serious consequence of both PK and DSEK, even despite maximal medical therapy in certain cases. DSEK has an equivalent incidence of IOP elevation to PK in comparable patients. Careful monitoring of IOP and appropriate therapy should be instituted to prevent progression to glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
(40 reference statements)
1
13
0
1
Order By: Relevance
“…Glaucoma is one of the most common complications after corneal transplantation and the degree of damage is generally linked to the surgical method, particularly PKP, DSEK and Boston artificial corneal transplantation ( 19 ). The postoperative incidence was 33.33%, which was consistent with that of previous studies ( 13 , 19 , 20 ). The incidence of postoperative glaucoma in the DSEK group of the present study was 34.21%, which was higher than that in previous studies, which reported incidences of 0-15% ( 21 , 22 ), but was similar to that in other studies that indicated that the incidence of glaucoma after DSEK may be as high as 35-39% ( 23 , 24 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Glaucoma is one of the most common complications after corneal transplantation and the degree of damage is generally linked to the surgical method, particularly PKP, DSEK and Boston artificial corneal transplantation ( 19 ). The postoperative incidence was 33.33%, which was consistent with that of previous studies ( 13 , 19 , 20 ). The incidence of postoperative glaucoma in the DSEK group of the present study was 34.21%, which was higher than that in previous studies, which reported incidences of 0-15% ( 21 , 22 ), but was similar to that in other studies that indicated that the incidence of glaucoma after DSEK may be as high as 35-39% ( 23 , 24 ).…”
Section: Discussionsupporting
confidence: 92%
“…Secondary glaucoma was defined as follows: IOP or estimated IOP ≥24 mmHg and requires intervention with IOP-lowering medication, postoperative IOP is 10 mmHg higher than the preoperative IOP, or the IOP cannot be controlled by drugs and surgical treatment is required (11)(12)(13)(14). Primary transplant failure refers to transparent persistent irreversible corneal edema after surgery (15).…”
Section: Pkpmentioning
confidence: 99%
“…However, many studies calculate the frequency of elevated IOP after keratoplasty by dividing the number of observed cases by the number of grafts performed during the study period. 1,9,13,14 Because many patients may not be followed long enough to note the onset of hypertony, such calculation methodology leads to an underestimation of true incidence. We used a survival analysis to provide more accurate assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Reduktion der Steroidtherapie unter Kontrolle gebracht werden [67]. Generell wird das Risiko nach DMEK für Augendruckanstiege, Glaukominduktionen oder -exazerbationen deutlich niedriger beziffert als nach DS(A)EK oder PKP [67,68]. Darüber hinaus ist aufgrund der weitaus selteneren immunologischen Abstoßung bei DMEK von einer kumulativ geringeren "Steroidlast" auszugehen als bei den beiden anderen kornealen Transplantationsverfahren.…”
Section: Seltenere Komplikationenunclassified